1998
DOI: 10.1111/j.1440-1681.1998.tb02220.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Blood Flow: Microvascular Anatomy and the Regulation of Medullary Perfusion

Abstract: 1. The microcirculation of the kidney is arranged in a manner that facilitates separation of blood flow to the cortex, outer medulla and inner medulla. 2. Resistance vessels in the renal vascular circuit include arcuate and interlobular arteries, glomerular afferent and efferent arterioles and descending vasa recta. 3. Vasoactive hormones that regulate smooth muscle cells of the renal circulation can originate outside the kidney (e.g. vasopressin), can be generated from nearby regions within the kidney (e.g. k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(113 citation statements)
references
References 75 publications
1
111
1
Order By: Relevance
“…A first example is the generation of vasodilatory prostaglandins through activation of cyclooxygenase (COX) (58). It has been observed that perfusion of the renal medulla is sensitive to COX inhibition (110,113,119). Furthermore, renomedullary interstitial cells have receptors for ANG II and BK and release PGE 2 in response to these agents (21, 72,178,179,186).…”
Section: Medullary Po2 and Perfusion Of The Medullamentioning
confidence: 99%
See 1 more Smart Citation
“…A first example is the generation of vasodilatory prostaglandins through activation of cyclooxygenase (COX) (58). It has been observed that perfusion of the renal medulla is sensitive to COX inhibition (110,113,119). Furthermore, renomedullary interstitial cells have receptors for ANG II and BK and release PGE 2 in response to these agents (21, 72,178,179,186).…”
Section: Medullary Po2 and Perfusion Of The Medullamentioning
confidence: 99%
“…1). For greater detail, the interested reader is directed to a number of well-illustrated sources (6,7,48,49,55,56,60,81,85,86,99,105,110,113,163).…”
Section: Renal Medullary Microvascular Anatomymentioning
confidence: 99%
“…PO 2 is ∼ 70 mm Hg in the cortex, ∼ 20 mm Hg in the outer medulla, and even lower in the inner medulla. Thus, the medulla is in a hypoxic environment under a physiological state [1] . Such an arrangement is strategically necessary to maintain the corticomedullary osmotic gradient for fluid absorption and urine concentration [2] .…”
Section: Kidneys Are Vulnerable To Inflammatory Insultsmentioning
confidence: 99%
“…Such an arrangement is strategically necessary to maintain the corticomedullary osmotic gradient for fluid absorption and urine concentration [2] . To avoid energy deprivation in the low pO 2 regions, an array of hormones, autocoids, and vasoactive substances, mostly synthesized in the medulla, including medullipin, prostaglandins, endothelins, nitric oxide, angiotensin II, kinins, and adenosine are required [1,3] . There is constant and complex interplay among these regulators to optimize regional microvascular blood flow to keep the O 2 supply adequate for tubular consumption.…”
Section: Kidneys Are Vulnerable To Inflammatory Insultsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Additionally, FB may entail a greater risk of complications in ECMO patients due to the use of systemic anticoagulation and greater degree of illness in these patients. 13,14 Previous studies have demonstrated the safety of FB in subjects receiving mechanical ventilation. 15,16 However, its safety profile in adult patients supported with ECMO is not well established.…”
Section: Introductionmentioning
confidence: 99%